CONDITIONS FOR INTEGRATING AND FACILITATING GENDER EQUALITY DURING MILITARY SERVICE - Sakhnii, Alina (Honor and Law, 2022)
The issue of achieving gender equality during military service has been studied. The actualization of this issue is due to the existence of cases of discrimination on the grounds of sex, despite the focus of public policy on ensuring equal rights and opportunities for men and women, especially including during military service. The article substantiates the need to integrate the gender component during military service, as well as indicates the impact of gender equality on the activities of military formations. A summary of the achievements in rule-making activities carried out with the aim of establishing equality between men and women, which testifies to the progressive gender prioritization. Quantitative indicators on the number of women in the Armed Forces of Ukraine are presented, which demonstrates the positive dynamics on gender issues. Given that the processes of reorientation and integration of the gender component in the security and defense sector are complex, lengthy and require comprehensive implementation, it was concluded that gender equality is needed at four levels (political, institutional, economic and social). Given that the processes of reorientation and integration of the gender component during military service are complex, long and also require comprehensive implementation. It was concluded that it is necessary to ensure gender equality at four levels (political, institutional, economic and social). The main conditions for effective integration and facilitation of gender equality in military service are highlighted, their content is revealed, and the most problematic issues that slow down their effective implementation are identified. It has been suggested that the relevance of improving existing legislation, educational work, the command's response to complaints of gender law violations, ensuring implementation in social roles, providing conditions for military service, and gender budgeting are the conditions for facilitating gender equality. It is impossible to implement the best practices of EU gender policy in Ukraine and achieve gender equality during military service without the above conditions. The advantages of introducing a gender component into the activities of military formations are indicated. There is a list of specific tasks, the phased implementation of which contributes to the goal of exercising equal rights and opportunities for women and men during military service.